Analyses of targeted/untargeted metabolites and reactive oxygen species of pepper fruits provide insights into seed browning induced by chilling. (1st December 2020) - Lee, Jeong Gu; Yi, Gibum; Choi, Jeong Hee; Lee, Eun Jin
Highlights: Severe seed browning of hot peppers occurred after 20 d at 2 °C. Increase in ROS is closely associated with seed browning. Tyrosine and phenylalanine were the major metabolites observed in brown seeds. The Jasmonic acid pathway is activated during storage at 2 °C. Abstract: Hot peppers are sensitive to low temperature, and seed browning significantly reduces the fruit quality. This study aims to clarify the mechanisms of seed browning in terms of metabolite changes. Metabolites were analysed during a 30-day-storage period at 2 °C and 10 °C. Gamma-aminobutyric acid, tyrosine, phenylalanine, and isoleucine concentrations were significantly higher at 2 °C storage than at 10 °C. Reactive oxygen species (ROS) generation was associated with seed browning. Transcription of jasmonic acid synthesis and ROS scavenging genes were higher in hot peppers stored at 2 °C than those stored at 10 °C. This study elucidated the mechanisms underlying seed browning and chill damage in hot peppers during storage at low temperatures and our findings may help improve hot peppers' quality following harvesting.